2015
DOI: 10.1111/iwj.12490
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors associated with the development of skin tears in hospitalised older persons: a case–control study

Abstract: To identify the risk factors associated with the development of skin tears in older persons four hundred and fifty three patients (151 cases and 302 controls) were enrolled in a case-control study in a 500-bed metropolitan tertiary hospital in Western Australia between December 2008 and June 2009. Case eligibility was defined by a skin tear on admission, which had occurred in the last 5 days; or, a skin tear developed during hospitalisation. For each case, two controls who did not have a skin tear and had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 17 publications
2
61
0
2
Order By: Relevance
“…Once skin is damaged, inflammation occurs as part of the wound‐healing process, and this often causes oedemas, resulting in worsening of the epidermal damage . It is therefore quite possible that the oedema identified in the earlier case control study , rather than being present before the skin tear occurred, was a result of the inflammatory response to the skin tear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once skin is damaged, inflammation occurs as part of the wound‐healing process, and this often causes oedemas, resulting in worsening of the epidermal damage . It is therefore quite possible that the oedema identified in the earlier case control study , rather than being present before the skin tear occurred, was a result of the inflammatory response to the skin tear.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective study tested whether a tool designed to measure the presence of the six characteristics identified in an earlier case control study as associated with an increased likelihood of developing a skin tear successfully predicted who developed a skin tear during a 10‐day follow‐up period. Unfortunately, it did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected on a broad range of individual characteristics, skin characteristics, and biophysical skin properties by a single investigator at two points in time, 6 months apart. The selection of individual and skin characteristics was based on the skin tear literature and factors that were reported to contribute to cutaneous ageing …”
Section: Methodsmentioning
confidence: 99%
“…A recent review of the literature identifying individual attributes or clinical characteristics that predicted the risk of skin tears in older adults found that the vast majority of articles were based on lower levels of scientific evidence including expert opinion, case series, and observational studies . Three studies that used advanced statistical modelling to predict the risk of tears were identified . The first study by Lewin et al used multivariate regression analyses of data obtained from a non‐matched case–control study that was conducted in a Western Australian tertiary hospital on participants aged over 50 years .…”
Section: Introductionmentioning
confidence: 99%